Intervention with the wellness therapy spiritual emotional freedom technique (SEFT) in cancer patients and with chemotherapy: A scoping review - Gayatri, Galih; Ni Kadek Diah Purnamayanti (Svāsthya: Trends in General Medicine and Public Health, 2024)
Patients with cancer undergoing chemotherapy often experience psychological and physical symptoms that affect their quality of life. The Spiritual Emotional Freedom Technique (SEFT) is a potential nonpharmacological intervention to address these issues. This study aimed to determine the effects of SEFT therapy in patients with cancer undergoing chemotherapy. A scoping review was conducted via Google Scholar to search for articles published between 2020 and 2024 with keywords related to SEFT, cancer, and chemotherapy. Eleven articles that met the inclusion criteria were analyzed. The review analyzed 11 studies published between 2020 and 2024, focusing on the impact of SEFT on various psychological and physical outcomes. The findings consistently demonstrate that SEFT therapy significantly reduces anxiety, stress, depression, and pain levels while improving sleep quality and overall quality of life in cancer patients receiving chemotherapy. The therapy typically involves 10-20 min sessions conducted 2-3 times per week, consisting of setup, tune-in, and tapping phases. SEFT's mechanism of action is theorized to involve the modulation of the hypothalamic-pituitary-adrenal axis and influencing neurotransmitter activity through the stimulation of acupressure points.  SEFT therapy shows promise as a complementary intervention for improving the well-being of patients with cancer undergoing chemotherapy. It addresses both psychological and physical symptoms and potentially enhances overall quality of life. Further research should compare the effectiveness of SEFTs with that of conventional methods and evaluate its long-term impact on cancer patients undergoing chemotherapy.